Fatal choice a pilgrim's guide to hell - Timmerman, John (Eugene, Oregon : Cascade Books, 2015)
Using Socratic dialogue to argue the evidence, Fatal Choice makes its case for an orthodox view of hell. But more than that, the narrator finds himself on an actual tour of hell with none other than Hieronymus Bosch, the master of paintings on hell, as his mentor.
Includes bibliographical references (pages 211-213).
Description based on print version record.
Keywords: Hell -- Christianity -- History of doctrines; Arts and religion; Bosch, Hieronymus, -- -1516 -- Criticism and interpretation; RELIGION / Christian Theology / Eschatology; Electronic books